An Improved Particle Swarm Optimization Method for Color Image Segmentation - Sheshathri, V; Sukumaran, S (International Journal of Computer Sciences and Engineering, 2019)
Color image segmentation can be treated as a process of dividing a color image into some constituent regions. This paper presents color image segmentation method using an Improved Particle Swarm Optimization (IPSO). The RGB color image taken as an input image and remove the noise using Gaussian filter. The obtained preprocessed image the components are separated and find the object regions separately. All the ungrouped pixels would be detected and put in the nearest region. The main purpose of proposed IPSO method is used to find the best values of thresholds, particles and position that can give us an appropriate partition for a target image. This method tries to treat pixels as particles and provide them search space and motivated with IPSO. It findings to better optimized region and produces more accurate segmentation results for color images. The proposed method is tested on different single and group of color images are taken as the input image and the experimental results demonstrate its effectiveness.